Правова природа адміністративної відповідальності неповнолітніх - Лесько, Наталія (Видавництво Львівської політехніки, 2013)
Problems of institute of administrative responsibility of minors are studied, the opinions of scholars in the sphere of administrative law are analyzed, on this basis new notion of administrative responsibility of minors is suggested. Administrative responsibility of minors – application of educational measures that are applicable to minors or administrative penalties to persons aged 16 – 18 years, guilty in committing of the administrative offense. Juvenile misconducts are so called barometer which determines morality level of the society. Illegal behavior of minor often starts from deviant activities and then overgrows into administrative offences. Insufficient and inopportune relation to administrative offences of children results in formation of their feelings of impunity and permissiveness. The aim of this work is studying of problems of administrative responsibility of minors and analyzing of ways of comprehension of administrative responsibility of minors.
Keywords: діти; неповнолітні особи; профілактика правопорушень; адміністративні правопорушення дітей; адміністративна відповідальність; адміністративні стягнення; заходи впливу